(untitled) (Annals of Medical Research, 2021)
Aim: The high risk pregnancies are defined as the pregnancies in which the mother or baby is more likely to become ill or die than usual or complications before or after delivery are more likely to occur than expected. Advanced age pregnancies (AAP) have traditionally been defined as age > 35 years at delivery and have been regarded as high risk pregnancies. The aim of this study is to determine the prevalence of AAP in Samsun . Material and Methods: In this cross-sectional records of 10.100 deliveries occurred between 01 January- 31 December 2004 at three hospitals with obstetrics and gynecology departments in Samsun were investigated. Statistical analysis was done by using the Chi -square test. Results: The prevalance of AAP was found to be 7.8% (787). There were 17(%2.2) multifetal pregnancies, 90 (%11.4) small for gestational age (SGA) babies among AAP. There were no statistical significance in the rate of stillbirths, cesarean sections, multifetal pregnancies and SGA between mothers aged 35-39 years and aged 40 years and above. Conclusion: It is known that AAP are risky for mother and fetus. Therefore strategies should be developed for improving the family planning services to decrease the AAP.